Epigenetic Characterization of CDKN1C in Placenta Samples from Non-syndromic Intrauterine Growth Restriction - López-Abad, Miriam; Iglesias-Platas, Isabel; Monk, David (Frontiers in Genetics, 2016)
The cyclin-dependent kinase (CDK)-inhibitor 1C (CDKN1C) gene is expressed from the maternal allele and is located within the centromeric imprinted domain at chromosome 11p15. It is a negative regulator of proliferation, with loss-of-function mutations associated with the overgrowth disorder Beckwith–Wiedemann syndrome. Recently, gain-of-function mutations within the PCNA domain have been described in two disorders characterized by growth failure, namely IMAGe (intra-uterine growth restriction, metaphyseal dysplasia, adrenal hypoplasia congenita and genital abnormalities) syndrome and Silver–Russell syndrome (SRS). Over-expression of CDKN1C by maternally inherited microduplications also results in SRS, suggesting that in addition to activating mutations this gene may regulate growth by changes in dosage. To determine if CDKN1C is involved in non-syndromic IUGR we compared the expression and DNA methylation levels in a large cohort of placental biopsies from IUGR and uneventful pregnancies. We observe higher levels of expression of CDKN1C in IUGR placentas compared to those of controls. All placenta biopsies heterozygous for the PAPA repeat sequence in exon 2 showed appropriate monoallelic expression and no mutations in the PCNA domain were observed. The expression profile was independent of both genetic or methylation variation in the minimal CDKN1C promoter interval and of methylation of the cis-acting maternally methylated region associated with the neighboring KCNQ1OT1 non-coding RNA. Chromatin immunoprecipitation revealed binding sites for CTCF within the unmethylated CDKN1C gene body CpG island and putative enhancer regions, associated with the canonical enhancer histone signature, H3K4me1 and H3K27ac, located ∼58 and 360 kb away. Using 3C-PCR we identify constitutive higher-order chromatin loops that occur between one of these putative enhancer regions and CDKN1C in human placenta tissues, which we propose facilitates expression.